The Assessment of public private partnership program in Egypt - Rady, Ali Mohamed Atef (KDI School, 2012)
This study aims to assess the Egyptian PPP performance and benchmark it with the Korean PPP model, taking into consideration that the Korean case is one of the standards or the best practice model, as during the last few years, South Korea is considered one of the world' top five in PPPs. The policy makers in Egypt claim that PPPs is successful and working properly as well. In this study, the researcher tests this assumption by surveying the opinion of 23 operational PPP projects in Egypt through a questionnaire to assess the PPP performance in Egypt. The Objective of this study is to show the reasons why the public private partnership program in Egypt has originally been less thriving than anticipated in attracting investment to selected projects. One side of the reasons is the government’s financing form and the short of funding in long-term projects which considered an obstacle to the progress of PPPs. Egypt has carried out PPP projects in infrastructure since 1990. The most successful of these have been in the transportation sector. A new PPP strategy was initiated in 2006 and a new framework PPP law was approved by parliament in May 2010 and came into force in July 2010, this law gave some hope that things will recover and advance regarding the PPP, as it minimizes the uncertainty for investors, and guarantees their requirements in regard to lending reliability and certainty to the PPP process. PPP Central Unit has been launched in the Ministry of Finance, but still the infrastructure sector needs to urgently apply public sector alterations to deal with supply-side limitations, which requires alterations in delivery methods, processes, procedures and institutional structures to be customized towards clientfocused outcomes. The political developments of early 2011 due to the Egyptian revolution are likely to cause the private sector and investors to be cautious due to increased uncertainty and highly political risks. This can be overcome by a strong commitment from the new government to develop PPPs. In addition, Investors need to update their studies about the Egyptian PPP to cope with the new political developments as well as managing fluctuations in foreign exchange rates. Maintaining investors means that there is enough competition in the market.
Thesis(Master) --KDI School:Master of Public Policy,2012
Keywords: Egypt, South Korea, Public Private Partnerships, PPP Comparative Study, Assessing Performance.